Injecting usability in m-commerce. (28th November 2005) - Chui, Yoon-Ping; Lee, Stephen Siang-Guan; Helander, Martin G.; Chong, Jazmin; , Tangsakul Lawan
The use of handheld devices such as mobile phones is a rapidly growing phenomenon in m-commerce. However, the small screen display of handheld devices is a real challenge to user interface designers who have to satisfy both the functional and sensory needs of users. This paper presents the results of two usability studies of a telecommunications service provider's WAP portal and offers some usability guidelines for the design of WAP portals.